Buletin Peternakan : Dinamika Ovarium pada Kuda Hasil Persilangan Pejantan Thoroughbred dengan Induk Lokal Indonesia - Muhammad Danang Eko Yulianto, Bambang Purwantara, Amrozi (Peternakan UGM, 2016)
The development of horse breeding industry in Indonesia was commenced through horse racing events held all over the country. It were accelerated by the development of Thoroughbred-Indonesian local Crossbred horses. There are many broodmares injured during their racing time and retired from the racetracks. They may still has a reproductive vigor to continue on producing offsprings.